Supporting People with Visual Impairments in Cultural Heritage: Survey and Future Research Directions - Sylaiou, Stella; Fidas, Christos (International Journal of Human–Computer Interaction, 2022)
This literature review surveys published research that aims to foster blind and visually impaired (VI) people’s engagement with cultural heritage. The reviewed papers cover a broad area of methodological approaches, outlining challenges and solutions for empowering VI people to enjoy cultural heritage sites and museums, mainly with the use of Information and Communication Technologies (ICT). Fifty (50) papers are included in this survey, published between 2008 and 2021. They mostly focus on multisensory, multimodal and interdisciplinary, ICT-based assistive human-centered computing approaches. These methods often optimize the VI user experience through an effort to gain an in-depth understanding of this special group’s needs. Moreover, several publications include user evaluations and empirical studies. Findings suggest that approaches tend to become more complex, multimodal, and multidisciplinary as time progresses. This leads to a discussion and conclusions suggesting future research directions in this domain. The proposed way forward relates to a synthesis of methodologies, scientific domains, and approaches into a more holistic, comprehensive, and synergetic model.